In vitro evaluation of oral contraceptives on long-tailed macaque (Macaca fascicularis) primary ovarian cells - Muhammed, Mikail; Tengku Azizan, Tengku Rinalfi Putra; Mohd Noor, Mohd Hezmee; Abu Hassim, Hasliza; Che'Amat, Azlan; Saleh, Annas Bin; Han, Mark Hiew Wen; Ab Latip, Mohd Qayyum (Elsevier Ltd, 2024)
Hormonal contraception has been advocated as an alternative population control method for the long-tailed macaque population, which has increased exponentially due to anthropogenic changes and incidental food subsidies from human food waste. Risks of increased zoonosis and conflict are imminent if the population growth of long-tailed macaques is unchecked. However, there's a gap in the literature about the effect of hormonal contraceptives on long-tailed macaque reproductive tissues cell line. The present study aims to investigate the effect of oral contraceptives (Nordette, Noriday, and Ella) on long-tailed macaque ovarian cells. We determine the cell viability and cytotoxicity as well as the morphological changes of the drugs on long-tailed macaque ovarian cells using the MTT assay, Acridine orange/propidium iodide double staining method, morphological examination, and the 4, 6-diamidino-2-phenylindole (DAPI) staining method. For the MTT assay, The drugs were dissolved in culture media before use to have a concentration ranging from 0.5 μg/mL, 2.5 μg/mL, 0.125 μg/mL, 0.0625 μg/mL, and 0.0315 μg/mL to have three replicates for each treatment. In contrast, the concentration of 0.0315 μg/mL was used for the morphological and histopathological analysis. The result of the study indicates that human oral contraceptives (Nordette, Noriday, and Ella) inhibit the growth of long-tailed macaque ovarian cells and induce apoptosis in a concentration- and time-dependent manner (at a concentration of 0.0315 μg/mL and an IC50 lower than 10 μg/mL), With a statistically significant value of ****P < 0.001 for each drug compared to the negative control. The result of the present study contributes toward addressing the gap in the literature on the effect of oral contraceptives in long-tailed macaque ovarian cells. Hence, we conclude that human oral contraceptives (Nordette, Noriday, and Ella) are safe and effective in long-tailed macaque ovarian cells as such could be used to develop non-invasive oral contraceptives for controlling the population of long-tailed macaques as an alternative population control method.